Taxes and Subsidies in the Input-Output Model - Atsumi, Hiroshi (Quarterly Journal of Economics, 1981)
This paper reexamines Metzler's analysis of the effects of taxes and subsidies on the competitive supply prices of output in Leontiefs system. It will be shown that Metzler's conclusions are valid even if one removes the assumptions made by Metzler, and that Allen's conclusion concerning the ad valorem tax is false. We present some interesting properties of Leontiefs system, and also provide a theorem on Metzler's matrix, proving it and deriving some useful properties on the inverse matrix of the input-output model